Micropropagação e conservação de Discocactus Zehntneri, Pilosocereus Gounellei e Stephanocereus Luetzelburgii, cactos nativos da Chapada Diamantina, Bahia - Marchi, Maria Nazaré Guimarães (2012)
The family Cactaceae has about 100 genera and 1500 species distributed in a wide variety of climates and ecosystems from northern Canada to Patagonia, being more abundant in arid and semiarid regions. Due to high diversity and value, especially ornamental, the Cactaceae have been severely impacted by predation as well as the destruction and fragmentation of habitats. This, consequently, has endangered many of its representatives. In this context, micropropagation and cryopreservation of seeds can be alternatives for the conservation of this family. The objective of this study was to establish protocols for in vitro germination, establishment and propagation and to evaluate the physiological quality of cryopreserved seeds from Discocactus zehntneri, Pilosocereus gounellei and Stephanocereus luetzelburgii. For in vitro establishment reducing the water potential of the culture medium did not reduce the germinability of P. gounellei and S. luetzelburgii and the activated charcoal accelerated the germination of D. zehntneri besides increasing the germination of S. luetzelburgii. Seeds of D. zehntneri are neutral photoblastic and constant and alternating temperatures did not affect germination, but the pre-soaking in gibberellic acid (GA3) increased their germination. MS/2 and MS media promoted the growth of P. gounellei and S. luetzelburgii, respectively, while subcultures potentiated the growth of the three species under study. Mechanical injuries did not favor in vitro morphogenesis of the species studied. However, 1.34 µM naphthaleneacetic acid (NAA), on average, increased the multiplication rate of P. gounellei and S. luetzelburgii while the longitudinal explants stimulated multiplication of the latter species. The best results for the multiplication of P. gounellei occurred in explants derived from older plants (106 weeks). The charcoal and butyric acid (IBA) did not potentiate the in vitro rooting of shoots for P. gounellei and shoots of this species and of S. luetzelburgii were acclimatized with more than 85% survival. The cryogenic treatment did not reduce the physiological quality of seeds compared to control. Thus, the use of cryopreservation is suggested for ex situ conservation of seeds of D. zehntneri, P. gounellei and S. luetzelburgii.